(untitled) (Research, Society and Development, 2022)
Active learning methods dynamize pedagogical practices and emphasize the protagonism of the students to develop activities that attribute real meaning to the knowledge. Therefore, this article aims to map the experiences, challenges, and perspectives from English Language teachers regarding the use of active learning strategies in their pedagogical practices. We conducted a field research, based on an exploratory-descriptive perspective and a qualitative approach. To collect the data, we interviewed five English teachers from two schools in the municipality of Sátiro Dias, Bahia, Brazil. The interviews were analyzed through content analysis. The results elucidate the discussions based on four categories of analysis: (i) Experiences and knowledge about active learning methos; (ii) Active learning in teaching practice; (iii) Challenges and difficulties during the use of active methodologies; and (iv) Resources and improvement for pedagogical practice. The interviewees know the benefits of active learning, but the use of these methods is still limited in terms of innovation and punctual in terms of planning and application. It is necessary to reinforce the role of the teacher in the process of creation, planning, and application of these methods in the classroom. The prospects for the performance of English teachers with the use of active learning strategies are promising and, at the same time, challenging. There are still many challenges regarding the use of active learning strategies in English language teaching, mainly related to lack of resources, student demotivation, and resistance when changing the teaching methodology.